2011
DOI: 10.1136/bcr.10.2011.4925
|View full text |Cite
|
Sign up to set email alerts
|

Superficial siderosis associated with abundant   and  -synuclein accumulation

Abstract: A Japanese male developed deafness, pyramidal signs and ataxia at age 50. A cerebrospinal fluid examination showed elevated levels of iron, transferrin and ferritin. Brain MRI showed atrophy of the cerebellum and pons as well as potential iron deposits on the surface of the brain. At autopsy, the brain weighed 1090 g and showed severe atrophy and necrosis of the cerebellum. No vascular malformation was observed. Extensive deposits of hemosiderin that were well stained with Berlin blue and ferritin immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…Cerebrospinal fluid tau protein is also elevated in superficial siderosis . Takao et al reported unique neuropathological findings of superficial siderosis at autopsy . Abundant tau deposits were notable in their case.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Cerebrospinal fluid tau protein is also elevated in superficial siderosis . Takao et al reported unique neuropathological findings of superficial siderosis at autopsy . Abundant tau deposits were notable in their case.…”
Section: Discussionsupporting
confidence: 78%
“…Abundant tau deposits were notable in their case. The distribution of NFTs and neuritic threads was consistent with stage III of Braak's classification . In addition, AT8‐immunoreactive pretangles and NFTs were observed in the cerebellum and locus ceruleus .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In comparison with previous neuropathological reports of infratentorial SS, gliosis and the neuronal loss in our case appeared to be milder.…”
Section: Cognitive Impairments and Cssmentioning
confidence: 70%